2012
DOI: 10.1007/s10903-012-9712-5
|View full text |Cite
|
Sign up to set email alerts
|

Redressing the Limitations of the Affordable Care Act for Mexican Immigrants Through Bi-National Health Insurance: A Willingness to Pay Study in Los Angeles

Abstract: The 12.4 million Mexican migrants in the United States (US) face considerable barriers to access health care, with 45 % of them being uninsured. The Affordable Care Act (ACA) does not address lack of insurance for some immigrants, and the excluded groups are a large proportion of the Mexican-American community. To redress this, innovative forms of health insurance coverage have to be explored. This study analyses factors associated with willingness to pay for cross-border, bi-national health insurance (BHI) am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
0
15
0
2
Order By: Relevance
“…Therefore, researchers have investigated disparities in health care access and utilization between US-born Mexican Americans and Mexican immigrants according to documentation status (7, 17, 45, 93, 105, 133, 135). These studies have found trends of improving access and utilization as legal status changes—for instance, going from being undocumented to having a permanent visa to being a citizen—for Latinos of Mexican origin as well as for other Latinos (93).…”
Section: Health Care Access and Utilization Trends For Latinosmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, researchers have investigated disparities in health care access and utilization between US-born Mexican Americans and Mexican immigrants according to documentation status (7, 17, 45, 93, 105, 133, 135). These studies have found trends of improving access and utilization as legal status changes—for instance, going from being undocumented to having a permanent visa to being a citizen—for Latinos of Mexican origin as well as for other Latinos (93).…”
Section: Health Care Access and Utilization Trends For Latinosmentioning
confidence: 99%
“…Another study found that Mexican immigrants in the United States return to Mexico regularly to receive hospital care for serious illnesses as a response to having limited access to care in the United States (44). The main predictors of health care use in Mexico are health need, lack of health insurance coverage in the United States, employment status, delays in seeking care, more recent immigration, limited English proficiency, and the need for prescription drugs (45, 131, 137). Additionally, cultural factors, such as language and providers’ attitudes, influence decisions about whether to utilize health care south of the border (128, 138).…”
Section: Primary Care Integration and The Health Of Latinosmentioning
confidence: 99%
“…Moreover, reliance on private clinics and pharmacies would place return migrants at increased risk of incurring catastrophic medical expenses and going without medical care, especially preventative treatment (Galárraga, Sosa-Rubí, Salinas-Rodríguez, & Sesma-Vázquez, 2010; King et al, 2009). Recent cross-border research shows that Mexican immigrants in the United States who return home expressly to seek medical care are heavily dependent on private clinics, rather than those affiliated with IMSS, ISSSTE, or Seguro Popular (González-Block, Bustamante, Sierra, & Cardoso, 2014; González-Block & Sierra-de la Vega, 2011). Research using Mexico's National Survey of Migration on the Northern Frontier shows that deported migrants have especially low access to care, which is exacerbated by poor self-rated health (Fernández-Niño, Ramírez-Valdés, Cerecero-Garcia, & Bojorquez-Chapela, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This is an anonymous and free Italian code that irregular/undocumented migrants can obtain in order to access health services. It is valid for 6 months and renewable and ensures equal access to all "urgent and essential" care for irregular/undocumented migrants [44].…”
Section: Migrants' Features According To Regularity Statementioning
confidence: 99%
“…The educational level was high in both groups. Employment and educational status are likely to have an impact on migrants' health outcomes [45] in the long term [44]. Signiicant diferences were found between regular/ documented and irregular/undocumented migrants as far as the following variables are concerned: Being under the care of a psychiatrist and treated with psychiatric medications, which were both more common in the former than in the later.…”
Section: Migrants' Features According To Regularity Statementioning
confidence: 99%